Software Market Combining User Experience Design and Data Protection in an Agile Software Development Process - GUSTAFSSON, DAVID; IRANZAMINI, ARYAN; MÖLLER, HENRIK; SJÖHOLM, ANTON; SKOGLUND, ANNA (My University, 2016)
The purpose of this thesis was to study how an Agile software development methodology would affect user experience design and data protection in a software development process. This was accomplished through the development of a platform called Software Market. The Software Market was created for the Gothenburg based company Software Skills, and its purpose is to connect companies and developers worldwide for shorter IT-projects. The Software Market was developed alongside a bachelor’s and a master’s thesis project. The process started out organized through the use of Scrum. Even though Scrum is an Agile practice, it was discarded in favor of a more fluid approach to Agile. This was necessitated by the complex and rapidly changing development environment where the other thesis groups were designing and developing related platforms. The user experience design benefited from this fluid approach to Agile due to its ability to rapidly respond to changing requirements. The added stress of evolving design considerations was overshadowed by the ability to quickly reach new design goals. The work with data protection can not be said to have benefited from the fluid Agile approach in the same manner. Since the work on the Software Market was production focused the security considerations tended to become secondary concerns. This was alleviated through the creation of the security design document that enabled the individual developers to implement a secure design in a more independent manner. Still, security would likely have benefited from the use of a more rigidly organized method. Overall we found that the Agile methodology was well suited for this project. Considering the many interactions and connections with other groups, we even deem it a necessity.
Keywords: Informations- och kommunikationsteknik; Data- och informationsvetenskap; Information & Communication Technology; Computer and Information Science